Import Substitution in Agrarian Sector as the Basis of Technological Breakthrough to Innovational Production - Slatvitskaya, Irina Ivanovna; Mironova, Daria Dmitrievna; Zibrova, Natalia Mikhaylovna; Romanova, Svetlana Valentinovna; Ryabocon, Natalia Anatolievna (International Journal of Economics and Financial Issues, 2016)
Under conditions of the complicated geopolitical situation the problem related to substituting import with goods manufactured inside the country is especially vexed. The goal of import substitution is to improve the economic and food safety of the country. In addition to creating and developing opportunities of quick transfer of economy to the mobilization mode under extraordinary circumstances and in the period of unfavorable external economic environment, import substitution allows to increase competitiveness of key industries of economy. The article shows conceptual basics of import substitution in the production of food commodities. It demonstrates the urgency of import substitution of agricultural goods not only under Russian conditions but also for other countries. It analyzes the essence of the import substitution as a combination of social relations in terms of substituting import products for national ones. Besides, the article shows possible areas of improving tools of state financial support through the example of tax incentives of import substitution in the agrarian sector of economy. Keywords: import substitution, agrofood market, food provision, food import substitution, tax incentives. JEL Classifications: O31, Q18